Effect of Colorful Food Photography and Consumer Intentions to Purchase Food and Beverages - Harinnita Detta; Zulaikha Shabrina Samsulhadi; Georgius Jonathan; Ahmad Iqbal Syarib (Green Publisher Indonesia, 2024)
This study intends to look into how consumers are affected differently by food advertising utilizing monochrome and colorful images in terms of pleasure, arousal, and buy intention. A design study was carried out randomly with 101 participants from various residences in Jabodetabek Area (Jakarta, Bogor, Tangerang, Bekasi), Indonesia. Participants voluntarily exposed themselves to food advertisements. According to this study, employing either monochrome or colourful food photography can positively influence customer’s intentions to purchase foods and beverages. The results demonstrate that colourful food photography increases customer buy intentions by making food products more enticing and beautiful. One of the few research projects comparing the effect of colorful food photography as an advertising and consumer intentions to purchase food and beverages. The previous understanding of the significance of visuals in social media advertising is also expanded by this research.